Effectiveness of Kemangi (Ocimum basilicum) Leaf Methanol Extract against Candida albicans Colonies - Tarsikah, Tarsikah; Widyana, Erni Dwi; Wulandari, Lisa Purbawaning (JURNAL INFO KESEHATAN, 2022)
Candida species, for women are the foremost common cause of parasitic contaminations. Candida species affect contamination in 75% of women and at slightest 6-9% of women involvement repetitive vulvovaginal candidiasis. Candida albicans (CA) accounts for 85-95% of yeast strains separated from the vagina. The treatment which has been administered for candida infections is antifungal drugs such as clotrimazole and fluconazole. When applied topically, synthetic antifungal drugs cause allergic reactions, resistance, and a burning sensation. It is necessary to conduct research on plant-based herbal medicine as an alternative treatment. Kemangi, also recognized as Ocimum Basilicum (OB), is a plant native to Indonesia which has medicinal properties. The objective of this study is to examine how effective OB methanol extract is against CA colonies. The study was performed at Brawijaya University's Microbiology Laboratory in Malang. The experimental laboratories with Posttest Only Control Group Design were employed in this study, with four repetitions of OB concentrations of 15%, 20%, 25%, 30%, and 35% against CA colonies. One-way ANOVA was utilized as the hypothesis test, with a significance level of 0.05. The results demonstrated that OB extract with a concentration of 15% was able to inhibit the growth of CA colonies. In the OB extract with a concentration of 35%, no CA colony growth was revealed. One-way ANOVA test obtained p 0.000 <0.05. Conclusion OB owns adequacy in restraining the development of CA organism with negligible murdering rate at a concentration of 35%.  Research required to be performed to identify the antifungal potential of OB extract in vivo.